Mobilising communities for Aedes aegypti control: the SEPA approach - Robert J. Ledogar; Jorge Arosteguí; Carlos Hernández-Alvarez; Arcadio Morales-Perez; Elizabeth Nava-Aguilera; José Legorreta-Soberanis; Harold Suazo-Laguna; Alejandro Belli; Jorge Laucirica; Josefina Coloma; Eva Harris; Neil Andersson (BMC, 2017)
Abstract Camino Verde (the Green Way) is an evidence-based community mobilisation tool for prevention of dengue and other mosquito-borne viral diseases. Its effectiveness was demonstrated in a cluster-randomised controlled trial conducted in 2010-2013 in Nicaragua and Mexico. The common approach that brought functional consistency to the Camino Verde intervention in both Mexico and Nicaragua is Socialisation of Evidence for Participatory Action (SEPA). In this article, we explain the SEPA concept and its theoretical origins, giving examples of its previous application in different countries and contexts. We describe how the approach was used in the Camino Verde intervention, with details that show commonalities and differences in the application of the approach in Mexico and Nicaragua. We discuss issues of cost, replicability and sustainability, and comment on which components of the intervention were most important to its success. In complex interventions, multiple components act in synergy to produce change. Among key factors in the success of Camino Verde were the use of community volunteers called brigadistas, the house-to-house visits they conducted, the use of evidence derived from the communities themselves, and community ownership of the undertaking. Communities received the intervention by random assignment; dengue was not necessarily their greatest concern. The very nature of the dengue threat dictated many of the actions that needed to be taken at household and neighbourhood levels to control it. But within these parameters, communities exercised a large degree of control over the intervention and displayed considerable ingenuity in the process. Trial registration ISRCTN27581154 .